Flower Development and Perianth Identity Candidate Genes in the Basal Angiosperm Aristolochia fimbriata (Piperales: Aristolochiaceae) - Pabón-Mora, Natalia; Suárez-Baron, Harold; Ambrose, Barbara A.; González, Favio (Frontiers in Plant Science, 2015)
Aristolochia fimbriata (Aristolochiaceae: Piperales) exhibits highly synorganized flowers with a single convoluted structure forming a petaloid perianth that surrounds the gynostemium, putatively formed by the congenital fusion between stamens and the upper portion of the carpels. Here we present the flower development and morphology of A. fimbriata, together with the expression of the key regulatory genes that participate in flower development, particularly those likely controlling perianth identity. A. fimbriata is a member of the magnoliids, and thus gene expression detected for all ABCE MADS-box genes in this taxon, can also help to elucidate patterns of gene expression prior the independent duplication of these genes in eudicots and monocots. Using both floral development and anatomy in combination with the isolation of MADS-box gene homologs, gene phylogenetic analyses and expression studies (both by reverse transcription PCR and in situ hybridization) we present hypotheses on floral organ identity genes involved in the formation of this bizarre flower. We found that most MADS-box genes were expressed in vegetative and reproductive tissues with the exception of AfimSEP2, AfimAGL6 and AfimSTK transcripts that are only found in flowers and capsules but are not detected in leaves. Two genes show ubiquitous expression; AfimFUL that is found in all floral organs at all developmental stages as well as in leaves and capsules and AfimAG that has low expression in leaves and is found in all floral organs at all stages with a considerable reduction of expression in the limb of anthetic flowers. Our results indicate that expression of AfimFUL is indicative of pleiotropic roles and not of a perianth identity specific function. On the other hand, expression of B-class genes, AfimAP3 and AfimPI, suggests their conserved role in stamen identity and corroborates that the perianth is sepal and not petal-derived. Our data also postulates an AGL6 ortholog as a candidate gene for sepal identity in the Aristolochiaceae and provides testable hypothesis for a modified ABCE model in synorganized magnoliid flowers.